Simulation-Based Optimization Methods Applied to Large Scale Water Systems Control - Niewiadomska-Szynkiewicz, Ewa; Blaszczyk, Jacek (2016 Intl IEEE Conferences on Ubiquitous Intelligence & Computing, Advanced and Trusted Computing, Scalable Computing and Communications, Cloud and Big Data Computing, Internet of People, and Smart World Congress (UIC/ATC/ScalCom/CBDCom/IoP/SmartWorld), 2016)
Recent progress in computer science put forwards the research, applications of simulation-based optimization methods in applied science and engineering. This paper is concerned with computational research for complex environmental systems. The simulation-based optimization approach, numerical techniques that optimize performance of system by using simulation to evaluate the objective value are reviewed, discussed. The attention is focused on the application of this approach to operational management of large scale water systems. The results of two case studies are presented, discussed - flood control in the multireservoir water system in Poland, optimal control of the water distribution system in Canada.